2005
DOI: 10.1074/jbc.m506254200
|View full text |Cite
|
Sign up to set email alerts
|

The Elicitation of Plant Innate Immunity by Lipooligosaccharide of Xanthomonas campestris

Abstract: Lipopolysaccharides (LPSs) and lipooligosaccharides (LOSs) are major components of the cell surface of Gram-negative bacteria with diverse roles in bacterial pathogenesis of animals and plants that include elicitation of host defenses. Little is known about the mechanisms of perception of these molecules by plants and about the associated signal transduction pathways that trigger plant immunity. Here we address the issue of the molecular basis of elicitation of plant defenses through the structural determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(183 citation statements)
references
References 41 publications
8
168
0
7
Order By: Relevance
“…4). Among the genes we detected, several were reported to be related to disease resistance, such as F-BOX STRESS INDUCED 2 (Maldonado-Calderon et al 2012), PEN3 (Xin et al 2013), RPM1-INDUCED PROTEIN KINASE (Feng et al 2012), WRKY108 (Higashi et al 2008 and BETA-1,3-GLUCANASE 2 (Silipo et al 2005). This observation supports the hypothesis that AP2 domain containing transcription factors are involved in the regulation of differentially expressed genes in bbr1.…”
Section: Ap2 Domain Containing Transcription Factors Is Involved In Tsupporting
confidence: 77%
“…4). Among the genes we detected, several were reported to be related to disease resistance, such as F-BOX STRESS INDUCED 2 (Maldonado-Calderon et al 2012), PEN3 (Xin et al 2013), RPM1-INDUCED PROTEIN KINASE (Feng et al 2012), WRKY108 (Higashi et al 2008 and BETA-1,3-GLUCANASE 2 (Silipo et al 2005). This observation supports the hypothesis that AP2 domain containing transcription factors are involved in the regulation of differentially expressed genes in bbr1.…”
Section: Ap2 Domain Containing Transcription Factors Is Involved In Tsupporting
confidence: 77%
“…This finding regarding flagellin does not imply that Xcc bacteria entirely escape detection by plant basal defense systems. For example, lipopolysaccharides, harpins, and cold shock proteins of X. campestris have been implicated as general elicitors of plant defense responses (Newman et al, 1995;Meyer et al, 2001;Felix and Boller, 2003;Kim et al, 2004;Silipo et al, 2005). Our results reveal that flagellin detection systems are apparently circumvented by Xcc bacteria, but plant-microbe interactions involve multiple layers of defense and counterdefense, and other elicitors of basal defenses remain that may limit plant colonization by Xcc.…”
Section: Organism-level Effects Of Flagellin Perceptionmentioning
confidence: 76%
“…In the xylem, Xcc growth causes darkening of the veins and eventual death of the infected tissue. Many aspects of Arabidopsis-Xcc interactions have been studied (Bent et al, 1992;Lummerzheim et al, 1993;Parker et al, 1993;Buell and Somerville, 1997;Hugouvieux et al, 1998;Godard et al, 2000;Korves and Bergelson, 2003;O'Donnell et al, 2003;Silipo et al, 2005). The extensive progress made by Boller and colleagues concerning Arabidopsis FLS2-mediated flagellin detection Zipfel et al, 2004) motivated our examination of Arabidopsis-Xcc interactions with respect to flagellin detection.…”
Section: Introductionmentioning
confidence: 99%
“…5,6,7,8 PAMPs include structures characteristic from pathogens such as b-glucan, polysaccharide chitin, ergosterol, lipopolysaccharides (LPS), flagellin and elongation factor-Tu. 9,10,11,12 Among these PAMPs, flagellin, a main component of the bacterial flagellum, has been the most extensively studied in regards to the recognition mechanism and signal transduction. 13,14,15,16 We previously reported that flagellin from the rice avirulent N1141 strain of gram-negative phytopathogenic bacterium, Acidovorax avenae, induces PTI including H 2 O 2 generation, while flagellin from the rice virulent K1 strain of A. avenae does not induce.…”
Section: Specific Induction Of Pti By Flagellin Of a Avenaementioning
confidence: 99%